2013
DOI: 10.1007/s00267-013-0186-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stocking Rate on the Variability of Peak Standing Crop in a Desert Steppe of Eurasia Grassland

Abstract: Proper grazing management practices can generate corresponding compensatory effects on plant community production, which may reduce inter-annual variability of productivity in some grassland ecosystems. However, it remains unclear how grazing influences plant community attributes and the variability of standing crop. We examined the effects of sheep grazing at four stocking rate treatments [control, 0 sheep ha(-1) month(-1); light (LG), 0.15 sheep ha(-1 )month(-1); moderate (MG), 0.30 sheep ha(-1) month(-1); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…Reports indicated that reduced root growth in the presence of grazing pressure might affect the rooting biomass contribution to the soil organic matter pool . Reduced root allocation usually influences soil carbon inputs and also decreases nitrogen retention within the soil . Our results confirm previous reports of positive impacts of grazing exclusion on soil nutrients …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Reports indicated that reduced root growth in the presence of grazing pressure might affect the rooting biomass contribution to the soil organic matter pool . Reduced root allocation usually influences soil carbon inputs and also decreases nitrogen retention within the soil . Our results confirm previous reports of positive impacts of grazing exclusion on soil nutrients …”
Section: Discussionsupporting
confidence: 89%
“…Continuous grazing put an additional pressure on ecosystems of such fragile soils with low vegetation cover. On the other hand, exclosure as a method of land restoration is said to increase SOC sequestration through higher above‐ and below‐ground biomass and species richness …”
Section: Discussionmentioning
confidence: 99%
“…This creates opportunities for less preferable species, for example, S. breviflora to establish dominance in the plant community, resulting in reduced evenness. Grazing‐induced increase in species dominance has been extensively reported in previous studies (Calvert, ; Du et al, ; Hiernaux, ; Milchunas, Sala, & Lauenroth, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…In general, the higher the stocking rate, the more negative the impact on soil properties. Stocking rates may have direct or indirect impacts on soil properties by influencing plant stands (Wang et al, ), soil and root respiration (Chen, Hou, Chen, Wan, & Millner, ), and animal behavior while grazing (Lin et al, ). An optimal stocking rate is difficult to define as it varies with various factors, such as grazing practices (Dong, Zhao, Wu, & Chang, ) and animal type. Geographical and climatic conditions have a fundamental effect on the soil biogeochemistry of grasslands in relation to grazing practices.…”
Section: Interactions Of Grass–climate–soil–human Activitymentioning
confidence: 99%
“…Grasslands, one of the largest terrestrial ecosystems in the world, are crucial for wildlife habitat (Galli et al, ), livestock forage (Odriozola, García‐Baquero, Laskurain, & Aldezabal, ), and the livelihoods of nearly 800 million people globally (FAOSTAT, ). In China, about 390 million ha of grasslands (Wang et al, ) cover 41% of the total land area (Anonymous, ). Of which, about 84% (or 330 million ha) is suitable for grazing, but a significant proportion has been degraded due to overgrazing (Wu, Zhao, Yu, Luo, & Pan, ), reclamation to croplands (Xu, Chen, Luo, & Lin, ), and exploitation of by‐products or mineral resources (Dong & Yang, ).…”
Section: Introductionmentioning
confidence: 99%